0682 Self-reported Sleep Duration And Fat-free Mass In Middle Aged And Older Adults. (12th April 2019) - Tan, Xiao; Benedict, Christian
Abstract: Introduction: A loss of fat-free mass which predominantly consists of skeletal muscles may lead to a variety of age-related diseases including sarcopenia. Accumulating evidence has shown that short or long sleep duration is linked to decreased fat-free mass. However, current studies regarding the association between sleep duration and fat-free mass are largely focused on younger adults. We utilized data from a Swedish cohort in order to better understand whether self-reported sleep duration is associated with fat-free mass among middle-to-older aged adults. Methods: Participants were 19, 709 adults aged 45-75 years (mean: 60.7 years) from the EpiHealth study. Habitual sleep duration was assessed by questionnaire, fat-free mass was estimated by bioelectrical impedance analysis (Tanita BC-418, Tanita Corp., Tokyo, Japan). Analysis of covariance adjusted for age, gender, fat mass, level of leisure-time physical activity, smoking, and alcohol intake was used to test the association between self-reported sleep duration and fat-free mass, followed with Bonferroni corrections for multiple comparisons. Results: Compared to a report of 7-hour/day sleep duration, both shorter (<6 hours per day) and longer (≥8 hours per day) sleep duration were linked to significant lower fat-free mass (P<0.001). Specifically, a 7-hour/day sleep duration was associated with an estimated of 0.41 (95% CI: 0.06-0.76), 0.39 (0.14-0.63), and 0.76 (0.26-1.26) kg greater fat-free mass, compared to sleep duration of <6, 8, and >=9 hours/day, respectively. Conclusion: Both short and long sleep duration are associated with lower lean body mass in middle-aged and older adults. Intervention studies are therefore warranted to further examine the cause and effect relationship between sleep duration and body composition in this population. Support (If Any): This work was funded by Åke Wiberg Foundation (M17-0088, M18-0169) (XT), Fredrik and Ingrid Thuring Foundation (2017-00313) (XT), Novo Nordisk Foundation (NNF14OC0009349) (CB), and Swedish Research Council (2015-03100) (CB).